KARAKTERISASI UBIKAYU (Manihot utilissima L.) LOKAL GUNUNG KIDUL - , M.IHSAN ROSYADI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The characterization study of Gunung Kidul landraces cassava (Manihot utilissima L.) aims to document and characterize several quantitative and qualitative characters which used as the identifier of a clone and determine its potential productivity in comparation with some national commercial clones. The study was started from November 2010 up to September 2011 at the experimental field of Agricultural Extension Agency Siraman II, Wonosari, Gunung Kidul. The data were obesrved at quantitative and qualitative characters which appear 3 months after planting (map), 6 map, 9 map, and at harvesting date. The result shows that Gunung Kidul landraces cassava clone can be differentiated based on 10 morphological characters